A new species of Graphomya Robineau-Desvoidy (Diptera, Muscidae) - Couri,Márcia S. (2005)
Graphomya Robineau-Desvoidy is known from 12 neotropical species, only two of them with occurrence in Brazil. A new species from the Amazon is described and illustrated - G. amazonensis sp. nov. This is also the first record of the genus to the Amazon State, Brazil.